2006
DOI: 10.3168/jds.s0022-0302(06)72140-3
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Quantitative Trait Loci Affecting Milk Production Traits on Bovine Chromosome 6 in a Chinese Holstein Population by the Daughter Design

Abstract: Fourteen microsatellite markers with a coverage of 63.5 cM on bovine chromosome 6 were selected, and 26 sire families with 2,260 daughters were analyzed for mapping quantitative trait loci (QTL) affecting 5 milk production traits in a Chinese Holstein population. In the analyses across 26 families and within the largest significant families with a one-QTL model fitted, a QTL near BMS470 was detected that affected fat yield at the 5% experiment-wide significance level. When a 2-QTL model was fitted in the acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
34
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 29 publications
5
34
1
Order By: Relevance
“…The information content across 14 families, family 3 and family 8 on chromosome 6 is plotted in Figure 1. This is calculated from variance of the conditional probabilities of inheriting a chromosomal region at each centiMorgan as a proportion of the variance when true descent is known (Chen et al, 2006).…”
Section: Information Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…The information content across 14 families, family 3 and family 8 on chromosome 6 is plotted in Figure 1. This is calculated from variance of the conditional probabilities of inheriting a chromosomal region at each centiMorgan as a proportion of the variance when true descent is known (Chen et al, 2006).…”
Section: Information Contentmentioning
confidence: 99%
“…In dairy cattle, MAS could be used to pre-select young candidate bulls prior to progeny testing, thus increasing selection differentials, shortening generation interval and increasing genetic gain. In dairy cattle a number of studies have shown that quantitative trait loci (QTL) can be detected and mapped in commercial dairy cattle populations using the daughter design strategy (Lipkin et al, 1998;Ron et al, 2001;Chen et al, 2006). Different studies have found a large number of QTL affecting milk production, and all 29 bovine autosomes have been suggested as harboring QTL for these traits (Khatkar et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In the cow, heredity accounts for 25-50% of the variation in milk production traits (21). As a consequence genotype-phenotype associations mapped as quantitative trait loci (QTL) for lactation-associated traits have been found on all 29 autosomes (10). However, only a few of the causal genes for these QTL have been identified.…”
mentioning
confidence: 99%
“…The contribution of genetic factors to lactation has been extensively studied in agricultural species such as the cow and sheep (2,10,17,20,30,34,37,47,54,60,62,68,75). In the cow, heredity accounts for 25-50% of the variation in milk production traits (21).…”
mentioning
confidence: 99%
“…Because Bell and his offspring were used in many countries, From Frozen semen samples of the 68 at-risk Chinese Holstein bulls were collected from the Beijing Dairy Center, the Tianjin Dairy Cattle Development Center, and the Hebei Breeding Bull Station, which are the main distribution centers for Chinese Holstein bulls and cows in Northern China. Genomic DNA (gDNA) was isolated according to a procedure previously described 2 and was adjusted to a final concentration of 200 ng/ml.…”
mentioning
confidence: 99%